Chronic administration of nandrolone increases susceptibility to morphine dependence without correlation with LVV-hemorphin 7 in rats. (October 2016) - Huang, Eagle Yi-Kung; Chen, Yuan-Hao; Huang, Tzu-Ying; Chen, Ying-Jie; Chow, Lok-Hi
Abstract: LVV-hemorphin 7 (LVVYPWTQRF; LVV-H7), an N -terminal fragment of the β-chain of hemoglobin cleaved by cathepsin D/pepsin, is an atypical endogenous opioid peptide that is found in high concentration in blood. LVV-H7 acts as a μ-opioid agonist and an inhibitor of insulin-regulated aminopeptidase. Subchronic administration of anabolic androgenic steroids (AAS) has been clinically proven to induce the synthesis of erythrocytes and increase hemoglobin concentrations. Patients with a history of AAS abuse are more susceptible to opioid abuse. We hypothesized that this association could be at least partially attributed to the sensitization of the mesocorticolimbic dopaminergic pathway by LVV-H7. Using the conditioned place preference test and neurochemical analysis, we investigated the possible mechanism underlying the effect of chronic nandrolone administration on morphine-induced reward and its correlation with LVV-H7 in rats. Either LVV-H7 may not sensitize the rewarding neural circuits or its inhibition on locomotor activity could mask reward-related behaviors. Chronic nandrolone pretreatment indeed caused a significant reward by low dose morphine, which did not cause any reward in control rats. However, coadministration of anti -LVV-H7 antiserum with nandrolone did not block this effect. This may rule out the possibility of the involvement of LVV-H7 in the action of nandrolone to intensify morphine-induced reward. Moreover, the serum level of LVV-H7 was mildly increased in response to chronic nandrolone administration in our animal model. According to the current clinical observations, we may conclude that the chronic administration of nandrolone can increase susceptibility to morphine dependence, but that this effect is not related to elevated LVV-H7. Highlights: LVV-H7 activates opioid receptors and dose-dependently reduced locomotor activity. Nandrolone pretreatment prior to CPP testing potentiated the reward of morphine. LVV-H7 antiserum coadministered with nandrolone did not have any blocking effect. AAS increases susceptibility to morphine dependence without correlation with LVV-H7.